THE TAX SYSTEM OF UKRAINE IN THE TRANSITION ECONOMY (Globalization and Business, 2018)
The relevance of the study of the tax system is due to the objective need for qualitatively new instruments of taxation influence on economic development. Nowadays, the tax system of Ukraine is predominantly fiscal; since fiscal and other functions of taxes are interrelated in inverse proportion,their implementation is problematic. Therefore, despite the existence of the thorough research of the tax system of the state, there is a need to substantiate the essence, objectives,principles and criteria of the effectiveness of this complex and large-scale process. Exploration of the theoretical and practical principles of the state tax system development in the context of the economy transformation, defines the main directions of the improvement of the tax system of Ukraine.The article specifies the peculiarities of the formation of the tax system of Ukraine, considers the components of the tax and describes them. It emphasizes the need to control the timely payment of taxes and fees. The article determines the deficiencies of the domestic tax system, such as inequality in taxation and discretionary application of tax norms. The efforts for the improvement of the tax system of Ukraine should be aimed at reforming tax authorities, which should correspond with the best European models,and at organization of educational work with the taxpayers of different age groups.